Transparent memory tests with even repeating addresses for storage devices - V. N. Yarmolik; I. M. Mrozek; V. A. Levantsevich; D. V. Demenkovets (Informatika)
The urgency of the problem of memory testing of modern computing systems is shown. Mathematical models describing the faulty states of storage devices and the methods used for their detection are investigated. The concept of address sequences (pA) with an even repetition of addresses is introduced, which are the basis of the basic element included in the structure of the new transparent march tests March _pA_1 and March _pA_2. Algorithms for the formation of such sequences and examples of their implementations are given. The maximum diagnostic ability of new tests is shown for the case of the simplest faults, such as constant (SAF) and transition faults (TF), as well as for complex pattern sensitive faults (PNPSFk). There is a significantly lower time complexity of the March_pA_1 and March_pA_2 tests compared to classical transparent tests, which is achieved at the expense of less time spent on obtaining a reference signature. New distance metrics are introduced to quantitatively compare the effectiveness of the applied pA address sequences in a single implementation of the March_pA_1 and March_pA_2 tests. The basis of new metrics is the distance D(A(j), pA) determined by the difference between the indices of repeated addresses A(j) in the sequence pA. The properties of new characteristics of the pA sequences are investigated and their applicability is evaluated for choosing the optimal test pA sequences that ensure the high efficiency of new transparent tests. Examples of calculating distance metrics are given and the dependence of the effectiveness of new tests on the numerical values of the distance metrics is shown. As well as in the case of classical transparent tests, multiple applications of new March_pA_1 and March_pA_2 tests are considered. The characteristic V(pA) is introduced, which is numerically equal to the number of different values of the distance D(A(j), pA) of addresses A(j) of the sequence pA. The validity of analytical estimates is experimentally shown and high efficiency of fault detection by the tests March_pA_1 and March_pA_2 is confirmed by the example of coupling faults for p = 2.